Tradisi Ngalab Barokah: Studi Analisis Perilaku Santri PP Nasy'atul Muta'allimin Gapura Sumenep - Aribuddin (LPTNU Sumenep, 2023)
Barokah is one of the studies that is of interest to everyone from outside and among the people of the Islamic boarding school itself. Academics who still believe in supernatural things will of course also be interested in searching, discussing, studying, studying the meaning of blessings until the Day of Judgment. Examining the meaning of barokah in relation to students' efforts to forge themselves would certainly be something phenomenal. This research will use qualitative research methods, this research is often referred to as naturalistic research because the research is carried out in a natural way. It is called a qualitative method because the data and analysis are qualitative. This research also uses qualitative-phenomenological theory which is based on traditional facts which are still ongoing traditions in Islamic boarding schools to this day. The purpose of this research is intended to be a living reference for all readers that unseen things such as blessings remain something valuable for the next life. Likewise, the author really hopes that this article will be able to actualize in a 'contextual' form the old traditions which are believed to be able to provide blessings. Our current traditions, such as visiting graves, arranging kiai sandals, cleaning the hut yard, and the tradition of tawassulan towards elders and ulama must be maintained. The students of the Nasy'atul Muta'allimin Islamic boarding school are the objects of this research. It turns out that this tradition is still believed to be an effort to obtain blessings and at the same time remains a basic need for the majority of society, both society in general, especially students in Islamic boarding schools. It is believed that without blessings, the knowledge gained in Islamic boarding schools will not bring much positive change to society, especially to oneself. It turns out that the basic materials of Islamic religious education are felt to be very important for society in an effort to strengthen the mental-spiritual nature of humans (especially the younger generation) amidst the identity crisis and the recent decline in morality of the nation's children.